MELAYU BANGKA LANGUAGE MAP IN SOUTH BANGKA REGENCY - Bowo, Tri Arie; Lubis, Donal Fernado; Affandi, Achmad; Affressia, Ricca (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
The aim of this research is to create documentation and vocabulary inventory as well as mapping of Melayu Bangka Language in South Bangka Regency. The data collection method in this research uses direct field methods. Data was taken from direct interviews with informants using 200 Swadesh words translated into the target language. This research has 53 observation areas which are representative of villages in South Bangka Regency. Based on the data collection that has been carried out, there are 159 informants from 53 observation areas with lexicon data totaling 31,800 lexicons/words. Data analysis that determines the status of language, dialect, subdialect, or speech difference in this study uses dialectometric calculations from Guiter. Based on dialectometric calculations, with the comparison language area (Toboali) there were sub dialectal differences in Air Gegas (43%), Payung (46%), Pulau Besar (42%), Tukak Sadai (39%), and Lepar (43%). Dialect differences exist in the language area in Simpang Rimba (53,5%). Language differences exist in the language area of the Pongok Islands (93,5%). Based on the analysis, it can be concluded that there are five subdialect differences, one dialect difference, and one language difference with the comparison language area. The recommendations for this research are further research as a determinant of language status in Simpang Rimba and Pongok Islands and the creation of a Regent's Regulation on Regional Language Preservation which contains the protection, use, development, and guidance of regional languages.